Os Salões Nacionais de Arte em Belo Horizonte na década de 1980: as especificidades dos salões temáticos - Ana Luiza Teixeira Neves (2014)
This dissertation shows a research realised about National Art Displays which had taken place in Belo Horizonte city in the first half of 80's, specifically the so-called Thematic Displays between 1979 and 1984. These National Art Displays that had been promoted by the TownHall of Belo Horizonte and which had lasted about 72 years, meant an important event to foster the grownth of national artistic circuit, meaning an opportunity of visibility for young artists and even so those known ones. There is also a point to be considered the fact that thebiggest part of selected art pieces have been integrated to the Art Museum of Pampulha's collection; thus, forming a set of works available to be studied. At first glance, it has shown at that moment the context of this decade as the return of painting. Secondly, it has revised theart displays history as a propagator institution of tendencies and production of that circuit. Following, its showed the trajectory of these Displays at the contemporaneity until 80s beginning. Because of that, one has opted for the Thematic Displays search presented eachchapter, through analysis and texts of art-critics who have kept up with the events and worksbelonged to the Art Museum of Pampulha's collection.